Effect of Quenching Media Variations on the Mechanical Behavior of Martensitic Stainless Steel - Hussein, Abbas Kh.; Abbas, Laith K.; Hasan, Wisam N. (Al-Khwarizmi Engineering Journal, 2019)
The purpose of this study is designate quenching and tempering heat treatment by using Taguchi technique to determine optimal factors of heat treatment (austenitizing temperature, percentage of nanoparticles, type of base media, nanoparticles type and soaking time) for increasing hardness, wear rate and impact energy properties of 420 martensitic stainless steel. An (L18) orthogonal array was chosen for the design of experiment. The optimum process parameters were determined by using signal-to-noise ratio (larger is better) criterion for hardness and impact energy while (Smaller is better) criterion was for the wear rate. The importance levels of process parameters that effect on hardness, wear rate and impact energy properties were obtained by using analysis of variance which applied with the help of (Minitab18) software. The variables of quenching heat treatment were austenitizing temperature (985 C˚,1060 C˚),a soaking times (50,70 and 90 minutes) respectively, Percentage of volumetric fractions of nanoparticles with three different levels(0.01, 0.03 and 0.08 %) were prepared by dispersing nanoparticles that are (α-Al2O3,TiO2 and CuO) with base fluids (De-ionized water, salt solution and engine oil).The specimens were tempered at 700°C after quenching of nanofluids for (2 hours).The results for ( S/N) ratios showed the order of the factors in terms of the proportion of their effect on hardness, and wear rate properties as follow: Austenitizing temperature ( 1060 C˚),Type of base media (salt solution), Nanoparticles type (CuO), Percentage of nanoparticles (0.08%) and Soaking time(90min) was the least influence while for the impact energy were as follows: Type of base media (oil), Austenitizing temperature (985C˚), Percentage of nanoparticles (0.01%), Nanoparticles type (α-Al2O3) and last soaking time (50min).